Scalp dermatoses: The patterns and impact on quality of life - Kalam, Shaziya; Betkerur, Jayadev; Ranugha, PSS; Shastry, Veeranna (Journal of Pakistan Association of Dermatologists, 2023)
Introduction: The scalp is unique due to high follicular density and sebum production. Scalp diseases can occur as primary diseases, part of generalized disease or as a part of systemic disease. Objectives: To study clinico-epidemiological profile of scalp dermatoses and their effect on quality of life (QoL). Methodology: Groups 1 and 2 containing 268 patients with primary scalp complaints (PSC) and 260 patients with no PSC but suffering from diseases where scalp involvement is expected were recruited. History taking, examination and relevant investigations were done. In Group 1, QoL was assessed using modified Dermatology Life Quality Index (DLQI). Results: A male preponderance (54.5%) and mean age of 37.17 years were seen in patients with PSC. Most patients came with itching (60.8%) while scaling (27.7%) was the common sign. Overall, scalp was the common initial site while frontal scalp was the predominant region. Pityriasis capitis, infections and psoriasis were common while sensitive scalp was rare. DLQI was less than 10 in majority (85.4%). Conclusion: Scalp dermatoses may be localized or the initial site of generalized dermatoses. The effect on QoL is minimal unless the disease is generalized. Limitations: Difficulty in assessing QoL in scalp dermatoses using questionnaire designed for generalized dermatoses.